Activation of TP receptors induces high release of PGI2 in coronary arteries of renal hypertensive rats. (September 2018) - Paula, T.D.; Silva, B.R.; Grando, M.D.; Souza, H.C.D.; Bendhack, L.M.
Abstract: Aim: To investigate the molecular mechanisms and cellular signaling pathways involved in the activation of TP receptors and the consequent induction of contractile responses in coronary arteries of renal hypertensive (2K-1C) rats. Methods and results: The coronary perfusion pressure (CPP) was lower in 2K-1C rats during increased coronary flow as measured by the Langendorff technique. The coronary contraction and relaxation were evaluated by vascular reactivity studies, and the molecular mechanisms were investigated on the basis of the protein expression of TP receptors, Cav-1, eNOS, COX-1, and COX-2, as measured by Western blot. The levels of eicosanoids were determined by ELISA immunoassay and analyzed by reverse-phase HPLC coupled to electrospray ionization mass spectrometry (HPLC-MS/MS). The metabolites from NO production were evaluated by the Griess reaction. The coronary arteries of 2K-1C rats expressed COX-2 to a larger extent and TP receptors to a lesser extent than the coronary arteries of normotensive (2K) rats. Selective COX-1 and non-selective COX inhibitors reversed the reduction in the contraction induced by TP receptors in the coronary arteries of 2K-1C rats. U46619, an agonist of TP receptors, induced a contractile response that was relaxed by acetylcholine (ACh). In the coronary arteries of 2K-1C rats, this ACh-induced relaxation depended on COX. The activation of TP receptors increased the production of PGI2 in the coronary arteries of 2K-1C rats. The results demonstrated that increased COX signaling in the coronary arteries of 2K-1C rats mediated the low levels of CPP, the contraction induced by the activation of TP receptors, and the endothelium-dependent relaxation. The vasodilator PGI2 seemed to be the major product. Conclusion: Activation of TP receptors increases production of PGI2 in coronary arteries of 2K-1C rats. Highlights: The coronary bed of 2K-1C rats is less resistant than the coronary bed of 2K rats. The coronary arteries of 2K-1C rats have increased expression of COX and decreased expression of TP receptors. COX products mediates TP receptor contraction and ACh relaxation in the coronary arteries of 2K-1C rats. The activation of TP receptors releases a large amount of PGI2 in the coronary arteries of 2K-1C rats.